Thirty‐day suicidal thoughts and behaviors among hospital workers during the first wave of the Spain COVID‐19 outbreak - Mortier, Philippe; Vilagut, Gemma; Ferrer, Montse; Serra, Consol; Molina, Juan D.; López‐Fresneña, Nieves; Puig, Teresa; Pelayo‐Terán, José M.; Pijoan, José I.; Emparanza, José I.; Espuga, Meritxell; Plana, Nieves; et al. (Depression and anxiety, 2021)
Background Healthcare workers are a key occupational group at risk for suicidal thoughts and behaviors (STB). We investigated the prevalence and correlates of STB among hospital workers during the first wave of the Spain COVID‐19 outbreak (March–July 2020). Methods Data come from the baseline assessment of a cohort of Spanish hospital workers (n = 5450), recruited from 10 hospitals just after the height of the coronavirus disease 2019 (COVID‐19) outbreak (May 5–July 23, 2020). Web‐based self‐report surveys assessed 30‐day STB, individual characteristics, and potentially modifiable contextual factors related to hospital workers' work and financial situation. Results Thirty‐day STB prevalence was estimated at 8.4% (4.9% passive ideation only, 3.5% active ideation with or without a plan or attempt). A total of n = 6 professionals attempted suicide in the past 30 days. In adjusted models, 30‐day STB remained significantly associated with pre‐pandemic lifetime mood (odds ratio [OR] = 2.92) and anxiety disorder (OR = 1.90). Significant modifiable factors included a perceived lack of coordination, communication, personnel, or supervision at work (population‐attributable risk proportion [PARP] = 50.5%), and financial stress (PARP = 44.1%). Conclusions and Relevance Thirty‐day STB among hospital workers during the first wave of the Spain COVID‐19 outbreak was high. Hospital preparedness for virus outbreaks should be increased, and strong governmental policy response is needed to increase financial security among hospital workers.